2022
DOI: 10.1155/2022/4230788
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Screening of Natural Compounds as Broad-Spectrum β-Lactamase Inhibitors against Acinetobacter baumannii New Delhi Metallo-β-lactamase-1 (NDM-1)

Abstract: Antibiotic resistance is one of the significant problems globally; there is an increase in resistance with introducing every new class of antibiotics. Further, this has become one of the reasons for arising of new resistance mechanisms in Acinetobacter baumannii. In this study, we have screened natural compounds as a possible inhibitor against the NDM-1 β-lactamase enzyme from A. baumannii using a combination of in silico methods and in vitro evaluation. The database of natural compounds was screened against N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
5
2
Order By: Relevance
“…Baicalein complex were generally lower than those of the Adapalene-NDM-1 complex, indicating that Baicalein may induce a more stable conformation of NDM-1 compared to Adapalene. This observation is inconsistent with a previous study by Vasudevan et al [44], where lesser uctuation was observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Baicalein complex were generally lower than those of the Adapalene-NDM-1 complex, indicating that Baicalein may induce a more stable conformation of NDM-1 compared to Adapalene. This observation is inconsistent with a previous study by Vasudevan et al [44], where lesser uctuation was observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Our analysis revealed that the RMSF values for the Baicalein-NDM-1 complex were generally lower than those of the Adapalene-NDM-1 complex, indicating that Baicalein may induce a more stable conformation of NDM-1 compared to Adapalene. This observation is inconsistent with a previous study by Vasudevan et al [32], where lesser uctuation was observed [32] Rg is a measure of the compactness of the protein structure, and it re ects the overall size and shape of the protein. The uctuations in Rg during MD simulation can provide insights into the conformational changes and exibility of the protein complex.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, a molecular docking study on the phenolic compound mangiferin showed that mangiferin interacted with NDM-1 catalytic amino acid residues through hydrogen bonding and hydrophobic interactions. Mangiferin was found to have a good docking score (-9.12 Kcal/mol) with NDM-1, compared to a docking score of -8.77 Kcal/mol for meropenem, indicating the possible biological activity of mangiferin as a carbapenemase inhibitor [63].…”
Section: Discussionmentioning
confidence: 95%